A Primary Retroperitoneal Mucinous Tumor. (19th March 2015) - Heelan Gladden, Alicia A.; Wohlauer, Max; McManus, Martine C.; Gajdos, Csaba
Abstract : A twenty-five-year-old female presented with a large retroperitoneal mass. Workup included history and physical exam, imaging, biopsy, colonoscopy, and gynecologic exam. After surgical resection, the mass was determined to be a primary retroperitoneal mucinous tumor (PRMT). Clinically and histologically, these tumors are similar pancreatic and ovarian mucinous neoplasms. PRMTs are rare and few case reports have been published. PRMTs are divided into mucinous cystadenomas, mucinous borderline tumors of low malignant potential, and mucinous carcinoma. These tumors have malignant potential so resection is indicated and in some cases adjuvant chemotherapy and/or surveillance imaging.